Understanding users' disengagement with wearable activity trackers - Gouveia, Rúben; Barros, Sergio; Karapanos, Evangelos (My University, 2014)
With an increasing emphasis on preventive and user-driven healthcare, the market of personal informatics tools for health, such as wearable activity trackers, has received rapid growth. However, recent research has shown that most activity trackers have failed to drive sustained engagement for the majority of users. With this study we present initial insights on a longitudinal study that seeks to understand how users disengage with activity trackers and the role of two design strategies for sustaining users' engagement: contextual information and evolving content.
Keywords: Activity trackers; Behavior change; Personal Informatics